Enhanced room temperature ferromagnetism in Cr-doped ZnO nanoparticles prepared by auto-combustion method *Project supported by the Office of Research, Innovation, and Commercialization (ORIC), MUST Mirpur (AJK). (April 2018) - Haq, Khizar-ul; Irfan, M.; Masood, Muhammad; Saleem, Murtaza; Iqbal, Tahir; Ahmad, Ishaq; Khan, M. A.; Zaffar, M.; Irfan, Muhammad
Abstract: Zn1− x Cr x O ( x = 0.00, 0.01, 0.03, 0.05, 0.07, and 0.09) nanoparticles were synthesized, by an auto-combustion method. Structural, optical, and magnetic characteristics of Cr-doped ZnO samples calcined at 600 °C have been analyzed by using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), UV–Vis spectroscopy and vibrating sample magnetometer (VSM). The XRD data confirmed the hexagonal wurtzite structure of pure and Cr-doped ZnO nanoparticles. The calculated values of grain size using Scherrer's formula are in the range of 30.7–9.2 nm. The morphology of nanopowders has been observed by FESEM, and EDS results confirmed a systematic increase of Cr content in the samples and clearly indicate with no impurity element. The band gaps, computed by UV–Vis spectroscopy, are in the range of 2.83–2.35 eV for different doping concentrations. By analyzing VSM data, significantly enhanced room temperature ferromagnetism is identified in Cr-doped ZnO samples. The value of magnetization is a 12 times increased of the value reported by Daun et al . (2010). Room temperature ferromagnetism of the nanoparticles is of vital prominence for spintronics applications.